Sony Pictures Entertainment, Inc. : a cybersecurity attack from North Korea (B) - Alexander, Meredith (SAGE Knowledge. Cases., 2017)
On November 24, 2014, Sony Pictures Entertainment, a subsidiary of Sony Inc., was the victim of an unprecedented cybersecurity attack launched by North Korean hackers. The attack was a result of the upcoming premiere of Sony;s film The Interview, a comedy based on a fictional attempted assassination of North Korean dictator Kim Jong-un. The group responsible subsequently threatened an attack on theaters choosing to show the film. Sony Pictures CEO Michael Lynton must decide whether or not to stop the movie;s release, while also protecting Sony's public image, maintaining distributor relations, minimizing revenue loss, and safeguarding employees data from further risk.